Political Polarization, Power and Public Health: What Should Organizations Know - Valiavska, Anna; Smith-Frigerio, Sarah (2020)
ABSTRACT This paper presents challenges public health officials (PHOs) experience in decision making around the SARS-CoV-2 pandemic. The paper presents two challenges, political polarization and power in workplaces, that have direct and substantial outcomes for organizations and employees. We argue that organizations are making decisions about the safety of employees and the future of work based on recommendations from PHOs, and these recommendations are warped by political polarization and power processes. Developing a nuanced and complex understanding of this process can allow us to build more streamlined, autonomous, and ultimately, more safety conscious decision-making processes for PHOS and our organizations. We conclude the paper outlining best practices for PHOs, organizations relying on PHOs to make workplace decisions, and future research recommendations. Keywords worker health, organizational decision making, public health officials, power, political polarization ABOUT THE AUTHOR/S Dr. Anna Valiavska University of Puget Sound Anna Valiavska works with organizations and community members on developing effective teams and positive supervision practices. She researches ways we can build inclusive organizations through practices, policies, and leadership. Dr. Sarah Smith-Frigerio Columbus State University Sarah Smith-Frigerio works in the areas of mental health communication, social media and social change, media representations, particularly of mental health concerns and disability, and crisis communication. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).